2023
DOI: 10.1111/ijd.16635
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous involvement in VEXAS syndrome: clinical and histopathologic findings

Abstract: Background VEXAS (vacuoles, E1 enzyme, X‐linked, autoinflammatory, somatic) syndrome is an autoinflammatory disease with frequent cutaneous manifestations. Methods We conducted a retrospective study of all patients with genetically confirmed VEXAS syndrome seen at our institution. Available clinical photographs and skin biopsy slides were reviewed. Results Cutaneous manifestations developed in 22/25 (88%) patients with VEXAS syndrome. From this group, 10/22 (45%) developed skin involvement before or at the tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 31 publications
1
29
0
3
Order By: Relevance
“…15 Leukocytoclasia has been found in up to two-thirds of skin biopsies, which led to classification as vasculitis in early case reports of VEXAS syndrome. 14,15 It has recently been demonstrated that the dermal infiltrates seen in VEXAS syndrome display the same "loss of function" mutations of the UBA1 gene as paired bone marrow samples; thus, the skin infiltrates are a direct consequence of mutated cell clones of inflammatory cells rather than the result of generalized pro-inflammatory activity. 16 Another characteristic of VEXAS syndrome is the presence of subcutaneous nodules histologically reminiscent of septal panniculitis, as well as erythematous periorbital edema.…”
Section: Clinical Presentationmentioning
confidence: 99%
See 2 more Smart Citations
“…15 Leukocytoclasia has been found in up to two-thirds of skin biopsies, which led to classification as vasculitis in early case reports of VEXAS syndrome. 14,15 It has recently been demonstrated that the dermal infiltrates seen in VEXAS syndrome display the same "loss of function" mutations of the UBA1 gene as paired bone marrow samples; thus, the skin infiltrates are a direct consequence of mutated cell clones of inflammatory cells rather than the result of generalized pro-inflammatory activity. 16 Another characteristic of VEXAS syndrome is the presence of subcutaneous nodules histologically reminiscent of septal panniculitis, as well as erythematous periorbital edema.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…In some cases, the skin infiltrations of VEXAS syndrome have been histopathologically characterized as neutrophil urticarial dermatosis (NUD), but unusually, these were sometimes accompanied by epidermal dyskeratosis 15 . Leukocytoclasia has been found in up to two‐thirds of skin biopsies, which led to classification as vasculitis in early case reports of VEXAS syndrome 14,15 . It has recently been demonstrated that the dermal infiltrates seen in VEXAS syndrome display the same “loss of function” mutations of the UBA1 gene as paired bone marrow samples; thus, the skin infiltrates are a direct consequence of mutated cell clones of inflammatory cells rather than the result of generalized pro‐inflammatory activity 16 …”
Section: Clinical Presentationmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Bei bis zu zwei Drittel der Fälle ist in Hautbiopsien eine Leukozytoklasie zu beobachten, was in frühen Fallberichten zum VEXAS-Syndrom zur Einordnung als Vaskulitis führte. 14,15 Es konnte kürzlich demonstriert werden, dass die dermalen Infiltrate beim VEXAS-Syndrom dieselben Loss-of-Function-Mutationen des UBA1-Gens aufweisen wie gepaarte Knochenmarksproben; die Hautinfiltrationen sind demnach unmittelbar auf die mutierten Zellklone der Entzündungszellen zurückzuführen und entstehen nicht infolge eines generalisierten proinflammatorischen Aktivierungszustands. 16 Charakteristisch für das VEXAS-Syndrom sind weiterhin subkutane Knoten, die histologisch an eine septale Pannikulitis erinnern, sowie periorbitale, rötliche, ödematöse Schwellungen.…”
Section: Klinisches Bildunclassified
“…Histologisch zeigen sich in der Haut meist superfizielle, mitunter auch tiefreichende Infiltrate unreifer myeloider Zellen (Metamyelozyten, Myelozyten, stabkernige Neutrophile), die von reifen Neutrophilen, auch Lymphozyten und Histiozyten sowie einem interstitiellen Ödem begleitet sind. In einem Teil der Fälle wurden die Hautinfiltrate des VEXAS‐Syndroms histopathologisch als neutrophile urtikarielle Dermatose (NUD) eingeordnet, wobei diese ungewöhnlicherweise mitunter von epidermalen Dyskeratosen begleitet waren 15 . Bei bis zu zwei Drittel der Fälle ist in Hautbiopsien eine Leukozytoklasie zu beobachten, was in frühen Fallberichten zum VEXAS‐Syndrom zur Einordnung als Vaskulitis führte 14,15 .…”
Section: Klinisches Bildunclassified